Improvement of the Cd and Zn phytoremediation efficiency of rice (Oryza sativa) through the inoculation of a metal-resistant PGPR strain. (September 2022) - Liu, Anran; Wang, Wenjing; Zheng, Xiaoyan; Chen, Xiancao; Fu, Wenting; Wang, Gang; Ji, Jing; Jin, Chao; Guan, Chunfeng
Abstract : Cadmium (Cd) and zinc (Zn) in contaminated soil inhibit rice yield and produce toxic effects on human body through rice accumulation. Plant growth promoting rhizobacteria (PGPR) assisted phytoremediation is an effective ecological measure to improve the remediation efficiency of heavy metal contaminated soil. The purpose of this study was to investigate the efficiency of the combination of rice and Cd/Zn-tolerant PGPR strain Bacillus sp. ZC3-2-1 for the remediation of Cd–Zn contaminated soil. Moreover, the effects of inoculations on rhizosphere bacterial communities and ion homeostasis of rice under Cd–Zn exposure will also be explored. The results showed that compared with the treatment without inoculation, ZC3-2-1 decreased the bioavailable Cd and Zn concentrations in soil by 39.3% and 32.0%, respectively, and increase the phytoextraction of Cd 2+ and Zn 2+ by rice to 48.2% and 8.0%, respectively. This inoculation process significantly increased the rice biomass, resulting that the contents of Cd 2+ and Zn 2+ per biomass unit of rice didn't change significantly. This fact meant that ZC3-2-1 could improve the phytoremediation efficiency of Cd–Zn contaminated soil by promoting the phytoextraction and immobilization of the metal, while might not affect the crop food safety. Besides, through regulation of the Na + and Mg 2+ concentration in rice, ZC3-2-1 played a positive role in maintaining ion homeostasis which was disrupted by Zn or Cd. Moreover, ZC3-2-1 could modulate the beneficial bacterial communities in rice rhizosphere soil, and then enhanced Cd–Zn immobilization and enzyme activities in soil, leading to the enhancement of rice growth and phytoremediation efficiency. Above all, this study provided novel insights into developing an efficient phytoremediation system and safe production of rice in Cd–Zn contaminated soil with the application of Bacillus sp. ZC3-2-1, as well as advance our understanding of the principles of rhizosphere bacterial community assemble and maintaining ion homeostasis in rice during this phytoremediation process. Graphical abstract: Image 1 Highlights: Heavy metal tolerant strain with PGP traits was characterized as Bacillus sp. ZC3-2-1. ZC3-2-1 inoculation improved the phytoremediation efficiency of heavy metal by rice. The inoculation promoted the extraction of Cd and the immobilization of Cd and Zn. Bacteria inoculation maintained ion homeostasis in rice. The inoculation modulated the rhizosphere beneficial bacterial community structure.